2022
DOI: 10.1093/texcom/tgac040
|View full text |Cite
|
Sign up to set email alerts
|

Local networks from different parts of the human cerebral cortex generate and share the same population dynamic

Abstract: A major goal of neuroscience is to reveal mechanisms supporting collaborative actions of neurons in local and larger-scale networks. However, no clear overall principle of operation has emerged despite decades-long experimental efforts. Here we used an unbiased method to extract and identify the dynamics of local postsynaptic network states contained in the cortical field potential. Field potentials were recorded by depth electrodes targeting a wide selection of cortical regions during spontaneous activities, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…However, when the afferent stimulation ceases, the spiking activity dies out. Mammalian brains, and most likely also insect and zebrafish CNS, have eigen activity as ever-changing ongoing spiking and membrane currents no matter whether they are stimulated or not, awake or at sleep (Rudolph et al, 2007 ; Yap et al, 2017 ; Stringer et al, 2019 ; Davis et al, 2020 ; Marques et al, 2020 ; McCormick et al, 2020 ; Siegle et al, 2021 ; Willumsen et al, 2022 ).…”
Section: Conceptual Obstaclesmentioning
confidence: 99%
See 4 more Smart Citations
“…However, when the afferent stimulation ceases, the spiking activity dies out. Mammalian brains, and most likely also insect and zebrafish CNS, have eigen activity as ever-changing ongoing spiking and membrane currents no matter whether they are stimulated or not, awake or at sleep (Rudolph et al, 2007 ; Yap et al, 2017 ; Stringer et al, 2019 ; Davis et al, 2020 ; Marques et al, 2020 ; McCormick et al, 2020 ; Siegle et al, 2021 ; Willumsen et al, 2022 ).…”
Section: Conceptual Obstaclesmentioning
confidence: 99%
“…These results are well known and indicate that 85%−95% of the spikes in a brain are autonomous. A recent large-scale study showed that external stimuli and various experimental conditions could modify fluctuations in the (multidimensional) human cortical field potential, but not perturb the underlying dynamics generating the fluctuations (Willumsen et al, 2022 ).…”
Section: Conceptual Obstaclesmentioning
confidence: 99%
See 3 more Smart Citations